2007
DOI: 10.1042/bj20061754
|View full text |Cite
|
Sign up to set email alerts
|

PPARα and AP-2α regulate bombesin receptor subtype 3 expression in ozone-stressed bronchial epithelial cells

Abstract: Previously, we found that bombesin receptor subtype 3 (BRS-3) significantly increased in an ozone-stressed airway hyperresponsiveness animal model and resulted in induced wound repair and protection from acute lung injury. In the present study, we determined molecular mechanisms of BRS-3 regulation in human BECs (bronchial epithelial cells) in response to ozone stress. Ten oligonucleotide probes corresponding to various regions of the BRS-3 promoter were used in EMSA (electrophoretic mobilityshift assays). Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…More recent studies demonstrate BRS-3 receptors are present on pancreatic islets [8] and BRS-3 knockout animals have altered plasma insulin levels and altered glucose transporter 4 function [28,30]. Furthermore, from target receptor deletion (knockout) and expression studies, it has been reported that the BRS-3-receptor is frequently over-expressed by various tumors [7,18,34,40], its presence plays a role in tumor invasiveness [13,15,18,57], a role in lung development, bronchial epithelial cell proliferation and lung injury [15,4143,53], a role in taste preference [63], social response/anxiety [61,62], and may play an important role in regulating gastrointestinal motility [32]. …”
Section: Introductionmentioning
confidence: 99%
“…More recent studies demonstrate BRS-3 receptors are present on pancreatic islets [8] and BRS-3 knockout animals have altered plasma insulin levels and altered glucose transporter 4 function [28,30]. Furthermore, from target receptor deletion (knockout) and expression studies, it has been reported that the BRS-3-receptor is frequently over-expressed by various tumors [7,18,34,40], its presence plays a role in tumor invasiveness [13,15,18,57], a role in lung development, bronchial epithelial cell proliferation and lung injury [15,4143,53], a role in taste preference [63], social response/anxiety [61,62], and may play an important role in regulating gastrointestinal motility [32]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies (Tan et al, 2006(Tan et al, , 2007 demonstrate that BB 3 receptors are expressed in the airway in response to ozone injury and that wound repair and proliferation of bronchial epithelial cells is accelerated by BB 3 receptor activation, suggesting that it may mediate wound repair. The mechanism of lung ozone injury mediation of the up-regulation of BB 3 receptors has been studied by examining proteins interacting with the BB 3 receptor gene promoter region (Tan et al, 2007). Activator protein-2␣ and peroxisome proliferator-activated receptor-␣ increased the ozone-inducible DNA binding on the BB 3 receptor gene promoter, suggesting that they are specifically involved in the BB 3 receptor up-regulation (Tan et al, 2007).…”
Section: Bb 3 Receptor In Diseasesmentioning
confidence: 99%
“…For the BB 2 receptor, such areas include its role in motility with mediation of the descending peristaltic reflex (Grider, 2004) its role in lung injury and development of lung diseases, particularly neonatal lung disease and bronchopulmonary dysplasia, in which Bn-like peptides and the BB 2 receptor were shown to play an important role in various animal models (Li et al, 1994;Sunday et al, 1998;Emanuel et al, 1999;Cullen et al, 2000;Ashour et al, 2006;Ganter and Pittet, 2006;Subramaniam et al, 2007), its role in sepsis and in small intestinal mucosal protection and prevention of injury (Assimakopoulos et al, 2004(Assimakopoulos et al, , 2005aDal-Pizzol et al, 2006;Higuchi et al, 2006;Kimura et al, 2006a,b), its role in satiety effects (Merali et al, 1999;Ladenheim and Knipp, 2007), and its CNS effects on memory, learning, various behaviors, and response to stress (Merali et al, 1999(Merali et al, , 2006Yegen, 2003;Moody and Merali, 2004;Roesler et al, 2004Roesler et al, , 2006ados Santos Dantas et al, 2006;Luft et al, 2006Presti-Torres et al, 2007. For the BB 3 receptor such areas include its possible role in lung development and responses to lung injury (Shan et al, 2004;Hou et al, 2006;Tan et al, 2006Tan et al, , 2007 and its possible role in regulation of aspects of gastrointestinal motility (Porcher et al, 2005).…”
Section: Therapeutic Implications Of Bombesin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrates [46] that ozone simulates AP-2 alpha and PPARalpha to increase the activity of the BB 3 -receptor gene promoter leading to increased BB 3 -receptor expression. An additional insight into a possible role for the BB 3 -receptor in the GI tract came from a recent receptor localization study [6] where the BB 3 -receptor was found in highest densities in myenteric/ submucosal ganglia and in the C-kit interstitial cells of Cajal.…”
Section: Iiidbb 3 Receptors-recent Advancesmentioning
confidence: 99%